Music Translation: Giving Back to the People their Rich Musical Heritage - Tejero, Helen S. (JPAIR Multidisciplinary Research, 2009)
Philippine traditional music is undoubtedly a very important part of our cultural heritage, and it is endangered of extinction; the need to take action is urgent. How to bring this music to the classroom and eventually to give back to the Filipino people their rich musical heritage provided the impetus for this research. With this vision-mission in mind, a series of field researches was conducted in Bontoc, Sadanga Mountain Province. Another study was also done on Mindanao Traditional Music, particularly on the Maranao, Maguindanao, Higaonon, Tiruray, Manobo, Bagobo and T’Boli, after an intensive training on Field Music Research at the University of the Philippines, with fieldwork practicum in Sadanga Mountain Province. To speed up the use of research findings, the Kariala Center for Music Traditions, Incorporated was founded. The following music materials were evolved in the Center: production of musical instruments, workbooks, librettos for musical plays/ operettas, ethnic-based compositions, tapes, CDs, VCDs and DVDs. These materials reached the classrooms and the performing groups through national, regional and local workshops, through music, concerts theatre performances, and through competitions.